Rancang Bangun 3D Oriented Mouse Controller Menggunakan Finite State Machine Berbasis Mikrokontroller Arduino - Firdy Yantama; Dahnial Syauqy; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Rapid developing technology on game created term Electronic Sport (esport). Many newcomer esport athletes rise in number . one of the favorite category on esport is first-person shooter (FPS). Esport athletes spend up 8 to 14 hours traning daily. While conventional players can spend up 2 to 6 hours daily. Sit still on front of computer for a long time makes their body lacks physical movement and can cause health threats. By creating custom controller system with physical appearance and functions like a real gun in FPS game, its player will have more body activity. This system give the user new experience in playing FPS games. System is using Arduino Uno with accelerometer and gyroscope from MPU-6050 with pointer of 3d oriented vector as output. Angle pointer from pitch and yaw using Complementary Filter calculation will determine the mouse movement.. Sistem will be implementing Finite-State Machine as main state and sub-state are needed for the sistem. Based on test to measure how stable and accurate the sensor, give error rate 0,861% and 1,61% for stable and accuracy respectively. The satisfication results of its users based on User Experience (UX) standards are Useful 76.64%, Accessible 76.38%, Usable 92.29%, and Desirable 78.05%..